The Analysis of Mandatory TOEFL Test Policy in University of Muhammadiyah Prof. Dr. HAMKA - Kaniadewi, Nita (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
Policy analysis is a form of thinking that requires humans or institutions to decide whether or not a policy has been or will be implemented. Policy analysis is also used at University of Muhammadiyah Prof. Dr. HAMKA (UHAMKA) as a reference material in implementing policies by the university. One of these policies is the policy for the TOEFL test in the Faculty of Teacher Training and Education (FKIP) UHAMKA environment. This policy requires students who will take the final exam, either through a thesis trial or through publication, to take the TOEFL test with a minimum score of 450. Because of this policy, this research was conducted to find the urgency of carrying out the TOEFL test for these students. This study uses qualitative research methods that focus on reality or facts that occur to the subject being studied. In addition, the population and sample of this study came from students who had taken the TOEFL test which was held at the Language Laboratory of FKIP UHAMKA. The sample of this study was selected using a purposive sampling technique which put forward certain reasons in selecting the sample. Furthermore, triangulation is used in this study. The triangulation of the data used a questionnaire as well as structured interviews. Then, the data obtained through questionnaires and also interviews were analyzed qualitatively descriptively. The expected results of this study are the urgency of the TOEFL test for students who want to take the final exam, followed by the issuance of a Decree from the Dean of FKIP University of Muhammadiyah Prof. Dr. HAMKA regarding the obligation to have a TOEFL certificate with a minimum score of 450 in the FKIP UHAMKA environment as one of the prerequisites for registering for the final exam, either through a thesis trial or through publication.